Síntese hidrotermal assistida por micro-ondas como metodologia sintética eficiente para obtenção da rede metalorgânica [ZN(BDC)(H2O)2]n - Wanderley, Kaline A.; Alves Júnior, Severino; Paiva-Santos, Carlos de Oliveira [UNESP] (Sociedade Brasileira de Química, 2011)
This work presents the optimization of the microwave-assisted hydrothermal synthesis of [Zn(BDC)(H2O)2]n . The reactions were carried out at the fixed temperature of 120 ºC for 10, 20, 30 and 40 min. Pure crystalline [Zn(BDC)(H2O)2]n was obtained in high yield (ca. 90%) with a reaction time of 10 min. The phase obtained and its purity was confirmed by Rietveld refinement, with a final value for Rwp/Rexp equal to 1.48. Increased reaction times (20, 30 and 40 min) favored the formation of unwanted by products, resulting in mixtures of several crystalline phases.
Microwave-assisted hydrothermal synthesis as an efficient method for obtaining [ZN(BDC)(H2O)2]n metal-organic framework
Keywords: metal-organic framework (MOF); microwave; Rietveld refinement